2001
DOI: 10.1080/01690960042000094
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of long distance number agreement in probable Alzheimer's disease

Abstract: Two cross-modal naming experiments examined the role of working memory in processing sentences and discourses of various lengths. In Experiment 1, 10 memory impaired patients with probable Alzheimer's disease (AD) and 10 healthy elderly control participants showed similar sensitivity to violations of subject-verb number agreement in a short sentence condition and similar degradation to this sensitivity in a long sentence condition. Performance in neither length condition correlated with performance on working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
0
42
1
2
Order By: Relevance
“…Thus, these results add to those of prior studies using production and comprehension methodologies that have also found either load and/or span to be significantly related to subject-verb agreement. The few prior studies that have failed to find this relationship (Almor et al, 2001;Bock & Cutting, 1992;McDonald, 2006) show numerical tendencies in the same direction; perhaps the lack of significance in those results is due to power, or to the difficulty of the materials or tasks used.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, these results add to those of prior studies using production and comprehension methodologies that have also found either load and/or span to be significantly related to subject-verb agreement. The few prior studies that have failed to find this relationship (Almor et al, 2001;Bock & Cutting, 1992;McDonald, 2006) show numerical tendencies in the same direction; perhaps the lack of significance in those results is due to power, or to the difficulty of the materials or tasks used.…”
Section: Methodsmentioning
confidence: 84%
“…Arguing against a tie between working memory and the processing of agreement are studies in which no detrimental effect of load has been found (McDonald, 2006), or that have failed to find a correlation between working memory span and performance on agreement tasks (Almor, MacDonald, Kempler, Andersen, & Tyler, 2001;Bock & Cutting, 1992, Experiments 1 and 3). These differences in results cannot be explained by the type of load used or by determining whether span was measured using 1,500 msec.…”
Section: Stimulimentioning
confidence: 99%
“…The spoken realization of agreement production appears as a good candidate for automaticity given that it meets with the usual characteristics of automatized processes like high speed, low error rate, lack of effort required, and absence of general capacity use. The hypothesis of an automatic computation of agreement in such local Spec-head configurations accounts for the reports that working memory abilities of unimpaired adults do not correlate with their agreement performance in such structures (Bock & Cutting, 1992), and that Alzheimer patients, in spite of their working memory impairment, have no trouble dealing with local agreement checking (Almor et al, 2001).…”
Section: Syntactic Structure Working Memory and Automaticitymentioning
confidence: 99%
“…However, according to the authors, this decrease would not be related to working memory since they reported no correlation between attraction errors and the performance of their participants in a working memory test. Along these lines, Almor and colleagues (Almor, MacDonald, Kempler, Andersen, & Tyler, 2001) reported that Alzheimer patients, who suffer from a severe working memory impairment, are able to process subject-verb dependencies just as well as their control group. In contrast, the processing of long-distance discourse dependencies like pronounantecedent relationships was found to be significantly affected in Alzheimer patients.…”
Section: Syntactic Structure Working Memory and Automaticitymentioning
confidence: 99%
See 1 more Smart Citation